The human DNA polymerase beta gene structure. Evidence of alternative splicing in gene expression. - Chyan, Y J (1994)
DNA polymerase beta (beta-pol) is a single-copy gene that is considered to be part of the DNA repair machinery in mammalian cells. Using two human genomic libraries we have cloned the complete human beta-pol gene and determined the organization of the beta-pol coding sequence within the gene. The human beta-pol gene spans 33 kb and contains 14 exons that range from 50 to 233 bp. The 13 introns vary from 96 bp to 6.5 kb. Information derived from this study was used in defining the location of a deletion/insertion type restriction fragment length polymorphism (RFLP) 5' to exon I of the human beta-pol gene. This RFLP was utilized in linkage analysis of DNAs from CEPH families and the results confirm the previous assignment of the human beta-pol gene to chromosome 8 (p12-p11). Analysis of mRNA from six human cell lines using the polymerase chain reaction showed the expression of two beta-pol transcripts. Sequence analysis revealed that the size difference in these transcripts was due to deletion of the 58 bp sequence encoded by exon II, suggesting that the smaller transcript results from an alternative splicing of the exon II sequence during processing of the beta-pol precursor RNA.